(untitled) (Journal of Comparative Social Work, 2019)
English Social work in Latin America is commonly associated with the struggle for citizenship, democracy, equality and universal access to social services, often with a strong political-ethical reference to structural change. Hence, the informal personal relations that have traditionally permeated many Latin American societies are often viewed as preventing social change and equality among their citizens. This article discusses how the emphasis on universal rights and citizenship in the social services in Brazil represents a significant historical gain on the one hand, but an obstacle to providing social care on the other. With support from empirical data produced during fieldwork conducted among social workers in Brazil, the article shows that relations based on personal connections and relations outside the public sphere are vital to providing social care. In professional practice, this seems to create a contradiction in social work. Fundamental values in social work, such as universal inclusion, respect and dignity are framed in an egalitarian discourse, but when implemented in practice, they are simultaneously dependent on the application of personal relationships associated with traditional hierarchical codes of interaction. Therefore, in order to promote social inclusion and other fundamental values in social work, it is necessary to recognize the limits of an egalitarian and reductionist understanding of citizenship, and include the cultural practices of employing personal relations in the provision of social care. Due to historical and social legacies of exploitation and inequality, this paradox seems to receive scant attention in the dominant literature about social work in Brazil. Spanish Ciudadanía en trabajo social en Brasil: Equilibrando los derechos universales y el cuidado individual El trabajo social en Latinoamérica se comúnmente asociado con la lucha por la ciudadanía, la democracia, la equidad y el acceso universal a los servicios sociales, frecuentemente con una referencia política y ética hacia el cambio estructural. Por tanto, la relación personal informal que tradicionalmente ha permeado muchas sociedades latinoamericanas es vista a menudo como un obstáculo para el cambio social y la equidad entre los ciudadanos. Este artículo debate acerca de cómo el énfasis en los derechos universales y la ciudadanía en los servicios sociales en Brasil, representa un avance histórico significativo, por una parte; pero a la vez un obstáculo para proveer cuidado social, por la otra. El artículo se apoya en datos empíricos producidos durante el trabajo de campo conducido con trabajadores sociales en Brasil, y muestra que las relaciones basadas en conexiones personales y fuera de la esfera pública, son vitales para la provisión de cuidado social. En la práctica profesional, esto parece crear una contradicción en el trabajo social. Valores fundamentales de la profesión, tales como inclusión universal, respeto y dignidad se hallan enmarcados en un discurso igualitario, pero cuando se implementan en la práctica, son simultáneamente dependientes de la aplicación de relaciones personales asociadas con los códigos jerárquicos y tradicionales de interacción. Por lo tanto, en aras de promover inclusión social y otros valores del trabajo social, es necesario reconocer los límites del entendimiento igualitario y reduccionista de la ciudadanía, e incluir prácticas culturales de empleo de relaciones personales en la provisión de cuidado social. Debido a los legados históricos y sociales de la explotación y la desigualdad, esta paradoja parece recibir escasa atención en la literatura dominante sobre el trabajo social en Brasil